RISK MANAGEMENT IN AGRICULTURE UNDER CLIMATE CHANGES - Njegomir, Vladimir; Tepavac, Rajko; Bikicki, Tamara (Economics of Agriculture, 2016)
Agricultural production is exposed to the effects of various risks, of which the production risks represent its specifcity, given that they stem from the fact that the production is done outdoor and that it encompass management of living beings. Climate changes directly affect the production risks of agricultural production. In the literature, climate change are relatively suffcient researched but there are scarce studies that deal with the theme of risk management in agricultural production and in particular the management of risks under climate changse. With this in mind as the goal of the paper we have determined the need to point out on the importance and forms of agricultural risk management under climate changes. In an effort to achieve the goal, in the paper we frst point out to the basic characteristics of agricultural production risk management and then we point to the application of preventive measures, the role of the state as well as the comparative role of insurance. As the impact of climate changes have strongly negative impact on insurance companies that provide insurance for agricultural risks, we consider the issue of wheatther the conclusion of agricultural insurance contracts should be mandatory or voluntary.